Whole limb kinematics are preferentially conserved over individual joint kinematics after peripheral nerve injury - Chang, Young-Hui; Auyang, Arick G.; Scholz, John P.; Nichols, T. Richard (Journal of experimental biology, 2009)
Biomechanics and neurophysiology studies suggest whole limb function to be an important locomotor control parameter. Inverted pendulum and mass-spring models greatly reduce the complexity of the legs and predict the dynamics of locomotion, but do not address how numerous limb elements are coordinated to achieve such simple behavior. As a first step, we hypothesized whole limb kinematics were of primary importance and would be preferentially conserved over individual joint kinematics after neuromuscular injury. We used a well-established peripheral nerve injury model of cat ankle extensor muscles to generate two experimental injury groups with a predictable time course of temporary paralysis followed by complete muscle self-reinnervation. Mean trajectories of individual joint kinematics were altered as a result of deficits after injury. By contrast, mean trajectories of limb orientation and limb length remained largely invariant across all animals, even with paralyzed ankle extensor muscles, suggesting changes in mean joint angles were coordinated as part of a long-term compensation strategy to minimize change in whole limb kinematics. Furthermore, at each measurement stage (pre-injury,paralytic and self-reinnervated) step-by-step variance of individual joint kinematics was always significantly greater than that of limb orientation. Our results suggest joint angle combinations are coordinated and selected to stabilize whole limb kinematics against short-term natural step-by-step deviations as well as long-term, pathological deviations created by injury. This may represent a fundamental compensation principle allowing animals to adapt to changing conditions with minimal effect on overall locomotor function.